Pengaruh Generativity, Experience Expectation dan Motivation Terhadap Visit Intention Pada Museum Mojopahit Mojokerto - Jeffry Andreanto Ferdian; Erna Andajani; Siti Rahayu (UNHI Press, 2021)
This research aims to determine the effect of generativity, experience expectation, and motivation on visit intention. The object that we use here is Mojokerto Mojopahit Museum. Data processing was carried out using the IBM SPSS 24 program, in addition, researchers used IBM AMOS 22 which will be used for the SEM method or Structural Equation Model. The data in this study will use primary data obtained from online questionnaires. Respondents in this study were 200 people who have an interest in coming to the Mojopahit Museum in Mojokerto and have a generative nature. Sampling used non-probability sampling techniques and convenience sampling. The results of this study will indicate a significant positive effect of generativity on experience expectation, then experience expectation on motivation, and the influence of motivation on visit intention at the Mojopahit Museum in Mojokerto.